Dental biofilm and its ecological interrelationships in ovine periodontitis - Borsanelli, Ana Carolina; Athayde, Flávia R.F. [UNESP]; Agostinho, Sabrina D. [UNESP]; Riggio, Marcello P.; Dutra, Iveraldo S. [UNESP] (Microbiology Society, 2021)
Introduction. Periodontitis, one of the most common oral disorders in sheep, is caused by a mixed and opportunistic microbiota that severely affects the health and welfare of animals. However, little is known about the ecological processes involved and the composition of the microbiota associated with the development of the disease. Hypothesis/Gap Statement. Using high-throughput sequencing of the 16S ribosomal RNA gene and network analysis it would be possible to discriminate the microbiomes of clinically healthy sheep and those with periodontitis and possibly identify the key microorganisms associated with the disease. Aim. The present study aimed to characterise the composition of dental microbiomes and bacterial co-occurrence networks in clinically healthy sheep and animals with periodontitis. Methodology. Dental biofilm samples were collected from ten sheep with periodontitis and ten clinically healthy animals. Bacteria were identified using high-throughput sequencing of the 16S ribosomal RNA gene. Results. The most prevalent genera in the dental microbiota of sheep with periodontitis were Petrimonas, Acinetobacter, Porphyromonas and Aerococcus. In clinically healthy animals, the most significant genera were unclassified Pasteurellaceae, Pseudomonas, and Neisseria. Fusobacterium was found at high prevalence in the microbiomes of both groups. The dental microbiota of sheep in the two clinical conditions presented different profiles and the diversity and richness of bacteria was greater in the diseased animals. Network analyses showed the presence of a large number of antagonistic interactions between bacteria in the dental microbiota of animals with periodontitis, indicating the occurrence of a dysbiotic community. Through the interrelationships, members of the Prevotella genus are likely to be key pathogens, both in the dental microbiota of healthy animals and those with periodontitis. Porphyromonas stood out among the top three nodes with more centrality and the largest number of hubs in the networks of animals with periodontitis. Conclusion. The dental biofilm microbiota associated with ovine periodontitis is dysbiotic and with significant antagonistic interactions, which discriminates healthy animals from diseased animals and highlights the importance of key bacteria, such as Petrimonas, Porphyromonas, Prevotella and Fusobacterium species.
Keywords: Dental biofilm; Dysbiosis; High-throughput sequencing; Networks; Periodontitis; Sheep